LINKING CRISIS AND EMERGENCY MANAGEMENT IN STRATEGIC MANAGEMENT PROCESS OF NGOs IN GAZA STRIP. - Elzaanin, Amina; ahadiat, ayi; jimad, habibullah (FEB - Universitas Lampung, 2020)
NGOs play an important and clear role in development and relief programs in Gaza Strip. Due to the political conditions that Gaza Strip is going through and to the limited services which are presented by the government in Gaza Strip. Although of the remarkable role of these organizations, they face problems and shortcomings in management in times of crises and emergencies. This study aims to show how to link crisis and emergency management to the process of strategic management of NGOs in Gaza Strip. This study sheds lights on some aspects of the functions of strategic management processes and also it investigates some aspects of the possibility of NGOs dealing with disasters in Gaza Strip. The descriptive analytical method was used to achieve the objectives of the study. The researcher used a questionnaire to collect data. The study sample consisted of 120 employees working in NGOs. The current study shows some weakness in crisis and emergency management. Furthermore, there is a positive relationship between the formulation, implementation and evaluation of strategy and crisis and emergency management for NGOs in Gaza Strip. The results showed that there is a statistically significant relationship at the significance level (a ≤ 0.05) between strategic management processes and crisis and emergency management in NGOs in Gaza Strip.